Between princesses and other jobs : a tale of Indrajit and fix - Butler, D.J (Tale Indrajit & Fix, 2024)
"Indrajit and Fix are the founding partners of the Protagonists, a jobber company in Kish. Since the seven great families of Kish farm out all tasks they and the city need doing, a jobber might one day unblock a well, the next man a tollgate for the fair, and on the third hunt down a murderer on the loose, all in a corrupt old city that isn't so much governed as kept barely in bounds. Indrajit is a poet of a dying race, looking for his successor. Fix is a failed monk, pining for his lost love. They're swordsmen and thinkers, heroes in their hearts and in their deeds. They also recover stolen documents, unravel financial fraud, escort shipwrecked diplomats, and hunt in the ruins beneath the city for missing academics. Meanwhile, the criminals they investigate, rival jobbers, sorcerers, spies, assassins, and other mysterious parties get more and more reason to want the Protagonists dead. Welcome to Kish"-- Provided by publisher.